Logical Analysis of Inconsistent Data (LAID) for a paremiologic study - Cavique, Luís (2011)
A paremiologic (study of proverbs) case is presented as a part of a wider project, based on data collected by thousands of interviews made to people from Azores, and involving a set of twenty-two thousand Portuguese proverbs, where we searched for the minimum information needed to identify the birthplace island of an interviewee. The concept of birthplace was extended for all respondents that have lived in any locations more than 5 years,unintentionally introducing inconsistencies in the data classification task. The rough sets differ from classical sets by their ability to deal with inconsistent data. A parallel approach to data reduction is given by the logical analysis of data (LAD). LAD handicaps, like the inability to cope with the contradiction and the limited number of classification classes, will be overcome in this version of Logical Analysis of Inconsistent Data (LAID).